Perceptions Of Cadets Djadajat Maritime Academy Towards Online Learning Methods During The COVID-19 Pandemic - Yuni Mariah; Simson Katiandagho; Rizal Hasim; Suwarso (LPPM AKMI SUAKA BAHARI CIREBON, 2023)
The education sector is included in the impact of the COVID-19 pandemic, thus encouraging adaptation activities to prevent the spread of the outbreak face-to-face learning in class is abolished and all learning is transferred to the network. This change in learning methods is certainly very influential on cadets in receiving and understanding learning materials from lecturers. This research was conducted to describe the cadet’s perception of the Djadajat Maritime Academy on the effectiveness of online learning. This study's research design makes use of qualitative research. Data was collected by questionnaire and was analyzed from percentage of tabulations data. The results show that online learning according to the cadets' perception is considered to have many limitations and is still less effective